2010
DOI: 10.4103/0019-5154.74536
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the autoantibody levels in relation to disease severity and therapy response in pemphigus patients

Abstract: Background:In pemphigus, autoantibodies are directed against adhesion molecules, which make the junctions between keratinocytes, and thus determining their level can reflect the disease activity.Aim:The purpose of this study is to determine the clinical significance of the autoantibody levels in pemphigus management.Materials and Methods:The clinical features of 47 pemphigus vulgaris patients were assessed and patients′ sera were investigated by indirect immunofluorescence using monkey esophagus as a substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
1
12
1
Order By: Relevance
“…In contrast, in this study, we also observed that IIF titers decreased dramatically after the introduction of immunosuppressive therapy in the majority of dogs with PF, as seen in other papers (Nishifuji et al, 2005;Aksu et al, 2010). A parallel relationship between IIF titers and disease activity was seen in two of the 14 dogs with PF.…”
Section: Discussioncontrasting
confidence: 56%
“…In contrast, in this study, we also observed that IIF titers decreased dramatically after the introduction of immunosuppressive therapy in the majority of dogs with PF, as seen in other papers (Nishifuji et al, 2005;Aksu et al, 2010). A parallel relationship between IIF titers and disease activity was seen in two of the 14 dogs with PF.…”
Section: Discussioncontrasting
confidence: 56%
“…Early reports suggested that the titers obtained by IIF could help to monitor therapy in these patients, but later studies raised doubts about the value of this test in the follow‐up of the disease. The issue remains a topic of debate …”
Section: Introductionmentioning
confidence: 99%
“…The issue remains a topic of debate. [1][2][3][4][5] The detection of circulating anti-Dsg1 and anti-Dsg3 antibodies using an enzyme-linked immunosorbent assay (ELISA) is of high diagnostic value in patients with pemphigus, and in the active phase, this test can help to establish the phenotype of pemphigus. [6][7][8] Patients with mucosal dominant PV typically demonstrate anti-Dsg3 antibodies only, while patients with mucocutaneous PV have both anti-Dsg3 and anti-Dsg1 antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that a false-positive result from IIF in our study was obtained from sera of two patients with toxic epidermal necrolysis. Table 4 demonstrates the sensitivity and specificity of IIF on different substrates including ME, guinea pig esophagus, and human tissues on different locations of the body for the diagnosis of pemphigus [2,7,9,14,15,20,24,27,[32][33][34]37]. For the sensitivity of IIF in the diagnosis of PV, HC was comparable to ME and guinea pig esophagus.…”
Section: Discussionmentioning
confidence: 97%
“…Monkey esophagus (ME) and guinea pig esophagus are well-accepted substrates for pemphigus vulgaris (PV) and pemphigus foliaceous (PF), respectively [11,14]. Sensitivity of IIF on ME ranged from 81 to 100 % [2,14,[32][33][34]37]. However, availability of monkey and guinea-pig esophageal tissues is sometimes limited due to ethical concerns relating to animal experimentation.…”
Section: Introductionmentioning
confidence: 99%